Economic assessment of transmission expansion projects in competitive electricity markets - an analytical review - Hesamzadeh, M.; Hosseinzadeh, N.; Wolfs, Peter (IEEE, 2008)
Restructuring of the electricity market has changed many aspects of the transmission system operation and planning. Reliability-Driven and Economic-Driven transmission expansion planning by regulated and private utilities are the substitutes of the traditional Cost-Driven transmission expansion planning. Reliability-based criteria for assessment of the transmission projects are almost well-developed while there exists a lack of a comprehensive framework for the economic evaluation of the transmission projects. Definition of a quantitative and monetary framework for economic evaluation of future transmission projects demands a detailed market analysis. In addition, specific characteristics and responsibilities of the transmission system in the open access structure must be understood comprehensively. To reaching the aforementioned goal, an analytical review on the existing economic assessment methodologies would be highly beneficial for the researchers in this area. Moreover, most of the review literatures on transmission investment in competitive electricity markets are general. These review literatures have tried to address all aspects of this challenging issue with devoting only few paragraphs to economic assessment of transmission projects. Given the aforementioned shortcomings, this article would bridge the gap by the following contributions: Firstly, reviewing available approaches for economic assessment of transmission projects based on research papers and industrial reports, Secondly, analysing the reviewed criteria critically by applying them to a modified Wood and Wollenberg 6-bus case study and Finally, summarizing the key components of a successful Economic Assessment Framework for transmission expansion or upgrade projects. Practical experiences of California Electricity Market, New England Electricity Market, Pennsylvania, New Jersey, and Maryland (PJM) and National Electricity Market, Australia have been accommodated in the article.